Organizational ambidexterity from the emerging market perspective: A review and research agenda. (24th April 2022) - Batra, Ishita; P, Preethi; Dhir, Sanjay
Abstract: Ambidexterity is an important driver of organizational success to meet the future needs of fast‐changing markets. Building on the organizational ambidexterity (OA) literature, this study investigates the concept of OA from the emerging market perspective. It adopts semantic network analysis and meta‐analysis to identify the factors affecting OA in emerging markets. Semantic network analysis measures degree and eigenvector centralities to understand how the studied words are connected to OA in emerging markets. Meta‐analysis summarizes the factors affecting OA in the emerging markets and categorizes them as homogenous or heterogeneous. The results reveal the homogeneity in factors such as firm age, firm size, research and development intensity, top management team (TMT) size, environment instability, ownership, competitive intensity, risk aversion, and international experience, and the heterogeneity in factors such as innovation, firm performance, technological turbulence, new product development, slack resources, TMT social, and market orientation. Future research directions and managerial implications are discussed.